"It Made Me Feel Comfortable Talking about Sex…": A Qualitative Content Analysis of Parent-Child Communications about Sexual Behavior with Gay Men. Issue 2 (4th March 2023) - Allen, Junior Lloyd
ABSTRACT: Introduction: Parent-child communications have historically played a critical role in helping to socialize adolescents' and young adults' attitudes toward sexual behaviors. However, there are limited studies that have examined the impact of parent-child communications with gay males, and sexual behaviors. Methods: Nineteen ( N =  19) Black/African American, Hispanic/Latino American, and White/Caucasian American gay males were asked about the impact of having communications with their parents on topics regarding sexual behavior and sexual identity. Interviews were transcribed using the iterative processes associated with thematic analysis. Results: For many of the participants, these conversations resulted in parent-child communications that were effective, especially regarding a) sexual safety, b) condom use, and c) comfort with talking about sex. For some, however, these conversations were most effective when they were single and non-monogamous. Lastly, a few participants stated that these conversations were not effective as the contents of the conversations did not apply to their sexual desires. Conclusion: For these participants, the conversations with their parents helped shaped their sexual behaviors and practices.